Inactivation kinetics and thermodynamics assessments of Geobacillus stearothermophilus during thermal sterilization for products safety - Augustine O. Ayeni; Ifeanyi T. Samuel; Bosede T. Adekeye; Oluranti Agboola; Obinna C. Nwinyi; Olagoke Oladokun; Ayodeji A. Ayoola; Francis B. Elehinafe (South African Journal of Chemical Engineering, 2022)
Chemical kinetics and thermodynamics provide modes and mechanisms for the thermal death of microbial spores. In this study, the effect of thermal inactivation on Geobacillus stearothermophilus, a highly heat-resistant bacterial species, was studied over the temperature range of 95, 100, 105, and 110 °C and holding sterilization periods of 10, 15, 20, 25, 30, and 45 min by the application of mathematical analysis of kinetic and thermodynamic properties. Thermal death rate constant, k, for the best kinetic order of sterilization ranged between 0.0431 to 0.1581 min−1 with the energy of activation, Ea, estimated to be 115.96 kJ/mol. Two primary thermal death kinetic models were applied (log-linear first order and the nonlinear Weibull). Weibull's model provided more reliable kinetic parameters to predict the effect of thermal treatments. Concave curves (α >1) were predicted with the Weibull's model for 100, 105, and 110 °C (1.57, 1.26, and 1.22 respectively), indicating the susceptibility of spores to lethal treatment. The rate parameter, ɸ (first reduction time) decreased with increasing thermal heating (28.80 min (95 °C), 21.08 min (100 °C), 14.61 min (105 °C), and 9.65 min (110 °C)) following the paths of the D-values (about 7 min to attain 88% spores’ destruction after 110 °C heating) of the log-linear kinetic model. Thermal death time (TDT) for the complete destruction of spores was predicted to be after 40 min at 110 °C. The z-value was 23.31 °C, indicating the sterilization temperature that must be attained for one log destruction of spores. The heat of activation showed endothermic reactions for all temperatures (∆H ranged 112.90 – 112.78 kJ/mol), Gibb's free energy of activation, ∆G, ranged from 325 – 333.74 kJ/mol (indicating a non-spontaneous reaction), and the entropy of activation (∆S) showed reversibility of reaction (∆S < 1) for all the thermal temperatures.